Review of flood stage frequency estimates for the City of Fort McMurray: Final report ... - Alberta Environmental Protection, Technical Services (University of Alberta Library, 1993)
This study was undertaken for the Technical Committee, Canada-Alberta Flood Damage Reduction Program in response to concerns raised by the City of Fort McMurray over the validity of the elevation established in previous studies as representing the 1 in 100 year design flood level. The specific objectives were first, to examine the historic data and assess it reliability and second, to update the flood frequency analysis, incorporating additional data collected in recent years. The main conclusions arising from the study are: a) In spite of some limitations, the information available on the 1875 ice jam event and most other historic events is considered to be sufficiently reliable for inclusion in the flood frequency analysis, b) the 1 in 100 year break-up stage at Fort McMurray based on the updated frequency analysis is 250.0 m, and c) The estimated return period for the 1875 event is in the order of 350 years and corresponds to a flood stage 2.0 m above the 1 in 100 year stage. Designation of flood risk ...